2010
DOI: 10.1590/s0004-28032010000100013
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects the liver and erythrocytes against oxidative stress in cirrhotic rats

Abstract: The data allow us to suggest that the observed oxidative stress is related to the damages caused by carbon tetrachloride and that the use of melatonin can minimize these damages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 43 publications
2
23
0
1
Order By: Relevance
“…39,58,61,62,63 The massive disarrangement of hepatic tissues architecture of untreated fibrotic rats (Group 3) correlated with the levels of alterations of serum indicators, namely, serum ALT, AST and ALP activities as well as serum TBC as previously described. 12,13,98,99 Additionally, photomicrograph section of hepatic tissues of fibrotic rats ( Figure 6) revealed and confirmed CCl 4 -induced necrosis and steatosis as previously described. 12,13,88,106 The localized distortions in hepatic architecture, persistence of hepatic steatosis and hydropic degenerations in fibrotic rats following treatment with raw and hydrothermal processed herbs were indications, which confirmed limited capacities of the herbs to ameliorate CCl 4 -induced morphological and functional impairments of hepatic tissues within the experimental period of 28 days.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…39,58,61,62,63 The massive disarrangement of hepatic tissues architecture of untreated fibrotic rats (Group 3) correlated with the levels of alterations of serum indicators, namely, serum ALT, AST and ALP activities as well as serum TBC as previously described. 12,13,98,99 Additionally, photomicrograph section of hepatic tissues of fibrotic rats ( Figure 6) revealed and confirmed CCl 4 -induced necrosis and steatosis as previously described. 12,13,88,106 The localized distortions in hepatic architecture, persistence of hepatic steatosis and hydropic degenerations in fibrotic rats following treatment with raw and hydrothermal processed herbs were indications, which confirmed limited capacities of the herbs to ameliorate CCl 4 -induced morphological and functional impairments of hepatic tissues within the experimental period of 28 days.…”
Section: Discussionsupporting
confidence: 83%
“…•− and Cl 3 COO •− radicals generated from CCl 4 metabolism promoted membrane lipid peroxidation, in which the erythrocytes 99 and hepatorenal tissues were vulnerable 1,9,11-14 and consequently, prompted rapid haemolysis and hepatic necrosis with attendant hyperbilirubinemia in the experimental rats (Groups 3-12). The results of the present study ( Figure 2) indicated that fibrotic rats, regardless of the type of herbal treatment administered, presented evidence of hyperbilirubinemia.…”
Section: Discussionmentioning
confidence: 99%
“…LPO levels, detected by the TBARS technique, were higher in the TAA group and reduced in both MLT-treated groups, suggesting its protective effect. In amitriptyline-induced hepatotoxicity, in cirrhosis by carbon tetrachloride use and by bile duct ligation, MLT-treated animals also achieved significantly lower LPO [41,[44][45][46]. Similar results were obtained with quercetin and glutamine in the treatment of TAA-induced ALF [16,39].…”
Section: Lipoperoxidationmentioning
confidence: 76%
“…Several studies have shown that melatonin administration has protective effects against cholestatic liver damage through its antioxidant, anti-inflammatory, and proapoptotic proprieties (19,28,29,46). Recently, studies have demonstrated the antiproliferative effects of melatonin on cholangiocytes in animal models of extrahepatic cholestasis as well as cholangiocarcinoma (26,44,45).…”
mentioning
confidence: 99%